Plan de Negocio para la creación de un restaurante especializado en alimentos saludables y veganos en la ciudad de Santa Marta (2022)
This business plan focuses on the adaptation of a contextual development framework for the definition of a business model oriented to the design and constitution of a company specialized in the preparation of healthy meals in the city of Santa Marta, based on the growing trend fitness – healthy that has begun to be coined worldwide in recent years. With the introduction of this business model, it is intended to respond to a new consumption trend that has presented a growing trend in adoption, for this, there will be an adequate functional, operational and commercial model to meet the needs of the target customer in a timely manner. This document carries out a mixed type of research, since a qualitative and quantitative model of recognition is implemented, for this, different instruments of a primary and secondary nature are used, seeking the global analysis of the object of study and formulation. At an institutional level, this research is carried out following the guidelines of the Organizational Management research area